Difference in the color stability of direct and indirect resin composites (Journal of Applied Oral Science, 2011)
Indirect resin composites are generally regarded to have better color stability than direct resin composites since they possess higher conversion degree. OBJECTIVE: The present study aimed at comparing the changes in color (ΔE) and color coordinates (ΔL, Δa and Δb) of one direct (Estelite Sigma: 16 shades) and 2 indirect resin composites (BelleGlass NG: 16 shades; Sinfony: 26 shades) after thermocycling. MATERIAL AND METHODS: Resins were packed into a mold and light cured; post-curing was performed on indirect resins. Changes in color and color coordinates of 1-mm-thick specimens were determined after 5,000 cycles of thermocycling on a spectrophotometer. RESULTS: ΔE values were in the range of 0.3 to 1.2 units for direct resins, and 0.3 to 1.5 units for indirect resins, which were clinically acceptable (ΔE